2017
DOI: 10.1080/14786419.2016.1277348
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the antiproliferative constituents and activity of Ficus exasperata (Vahl) on ovarian cancer cells –a preliminary investigation

Abstract: Ovarian cancer is one of the most common gynaecological cancers today. This study therefore investigates the anticancer effects of Ficus exasperata extracts and fractions on ovarian cancer cells. The antiproliferative activity of the crude extracts (1 mg/mL) was assessed using the MTT assay on A2780 (ovarian cancer) cell line. Bio-activity guided fractionation was performed and preliminary identification was further achieved using high resolution mass spectrometry and nuclear magnetic resonance spectroscopy. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…Phloridzin (Choi 2019) and linoleic acid (Lu et al 2010) are known to suppress tumor growth by inducing oxidant stress, blocking cyclin-dependent kinases and inducing apoptosis. However, the antiproliferative effect of F. exasperata observed in the current study was previously reported on ovarian cancer cells (Bafor et al 2017), which may be due to its contain in docosane, cardanol and chlorogenic acid. The anti-proliferative potentials of P. muellerianus and F. exasperata could be associated to their ability to modulate calcium in ux in the cells.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…Phloridzin (Choi 2019) and linoleic acid (Lu et al 2010) are known to suppress tumor growth by inducing oxidant stress, blocking cyclin-dependent kinases and inducing apoptosis. However, the antiproliferative effect of F. exasperata observed in the current study was previously reported on ovarian cancer cells (Bafor et al 2017), which may be due to its contain in docosane, cardanol and chlorogenic acid. The anti-proliferative potentials of P. muellerianus and F. exasperata could be associated to their ability to modulate calcium in ux in the cells.…”
Section: Discussioncontrasting
confidence: 66%
“…Although Tang et al (2010; and Bafor et al (2017) have reported the bene cial effects of some Phyllanthus sp and F. exasperata, respectively on MeWo prostate cancer and A2780 ovarian cancer cells, their effects on PC-3 cells have not been investigated. We characterized P. muellerianus and F. exasperata extracts by LC-MS analysis and determined their in vitro antioxidant potentials by DPPH assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies describe the anticancer potential of Ficus spp, ex. Ficus carica [ 46 , 47 ], Ficus salicifolia [ 46 ], Ficus religiosa [ 48 ], Ficus beecheyana [ 49 ], Ficus pandurata H [ 50 ] and Ficus exasperata (Vahl) [ 51 ], against various cancer cell lines, however, to the best of our knowledge, this is the first report showing Ficus sur stem bark extracts as a possible source of antineoplastic molecules.…”
Section: Resultsmentioning
confidence: 99%